Nurtipulse protainer: transforming fitness with personalised tracking and supplementation insights - Zamri, Fatin Nur Shahira; Linoby, Adam; Sanuddin, Nurul Diyana; Adnan, Mohd Aizzat (Universiti Teknologi MARA Cawangan Johor Kampus Pasir Gudang, 2025)
The NurtiPulse Protainer is a revolutionary fitness application that combines personalised supplementation insights with exercise monitoring, providing users with a comprehensive approach to enhancing their overall well-being and exercise performance. The program is a comprehensive fitness solution that integrates user-focused features, evidence-based recommendations, and cutting-edge analytics. Traditional fitness monitors frequently lack personalisation and fail to consider the role of supplementation in improving physical performance. Consequently, the application was created to address these limitations. NurtiPulse Protainer integrates seamlessly with wearables, nurtures a vibrant community for shared motivation and support, and delivers tailored fitness and supplementation plans by leveraging advanced technology and scientific research. Expert consultations, access to educational content, supplementation monitoring, performance analytics, and a user-friendly interface are among its primary benefits. This unparalleled user experience is guaranteed by the unique integration of scientific credibility and exercise and supplementation insights. NurtiPulse Protainer promotes health awareness, encourages natural supplementation, and reduces dependence on synthetic alternatives, thereby positively contributing to socio-economic and socio-environmental objectives. The app is a prominent solution in the fitness and wellness market due to its premium features, compatibility with wearables, and partnerships with wellness brands, which have a strong commercialisation potential. It is the optimal choice for individuals who are interested in a personalised, sustainable, and science-driven fitness voyage.